Risk factors associated with anastomotic leakage in patients operated due to colorectal tumour - Onder Altın; Murat Alkan (Medicinski glasnik, 2019)
Aim: To evaluate risk factors that may cause anastomotic leakage (AL) in patients who underwent resection and anastomosis due to colorectal cancer. Methods: Patients who underwent resection and anastomosis due to colorectal cancer between January 2014 and July 2018 in our clinic were included into the study. The patients were divided into two groups as ones with AL being Group 1, ones without AL being Group 2. Parameters related to the clinical characteristics, surgical and pathologic results in both groups were evaluated with univariate and multivariate analyses. Results: A total of 302 patients were included in the study. The AL was observed in 24 (7.9%) patients. Mortality was observed in five (20.8%) and six (2.2%) patients in Group 1 and Group 2, respectively (p=0.001). Significant risk factors for AL in the univariate analysis were coronary artery disease (CAD), chronic obstructive pulmonary disease, high American Society of Anesthesiologists (ASA) score, emergency surgical intervention, absence of preoperative intestine preparation, performed perioperative blood transfusion, tumour T stage, and neoadjuvant chemo-radiotherapy application. Only CAD and neoadjuvant CRT were determined as the independent risk factors for AL in the multivariate analysis. Conclusion: The AL developing after colorectal surgery continues to be an important problem thereby increasing mortality and morbidity along with its negative effect on hospitalization time and functional and oncologic results. Despite several studies on the topic, it is still very difficult to estimate the AL possibility in advance. Therefore, avoiding anastomosis in high risk patients may perhaps be the best option.
Keywords: cancer; morbidity; mortality